Adherence Towards Ventilator Associated Pneumonia Guidelines of Nurses Working in Critical Care - Zahra, Hina; Zaffar, Aliza; Saleem, Neelam; Fatima, Arooj (Biological and Clinical Sciences Research Journal, 2025)
Ventilator-associated pneumonia (VAP) is a significant cause of morbidity and mortality in critically ill patients. Nurses' adherence to VAP prevention guidelines plays a critical role in reducing the incidence of this infection. However, various institutional and personal barriers can impact compliance rates in clinical settings. Objective: To assess the adherence of critical care unit (CCU) nurses to ventilator-associated pneumonia (VAP) guidelines and identify factors influencing this adherence. Methods: A cross-sectional study was conducted in the Critical Care Department of Medicare Hospital, Multan, from January 2024 to January 2025. A total of 100 nurses working in the ICU and CCU departments were included in this study, which employed convenience sampling. Data were collected using a structured questionnaire consisting of three parts: demographic information, VAP guideline adherence (scored on a validated scale), and perceived barriers to compliance. Statistical analysis was performed using SPSS version 25. Mean adherence scores were compared across different variables using appropriate statistical tests, with a significance level set at p < 0.05. Results: The mean adherence score was 28.9 ± 4.04 (range: 17–34). Among the participants, 25% demonstrated good compliance, 30% satisfactory compliance, and 45% poor compliance with VAP guidelines. Significant barriers identified included staff shortage (70%), forgetfulness (65%), cost-control policies (60%), outdated education (44%), and fear of poor patient outcomes (42%). Nurses managing more than 20 ICU beds had adherence scores 8.0 points higher than those working fewer than 10 beds (p < 0.001). Additionally, nurses with prior education on VAP guidelines scored 0.8 points higher than their counterparts. Conclusion: Adherence to VAP guidelines among ICU nurses is suboptimal, with a significant proportion demonstrating poor compliance. Higher adherence was associated with more enormous ICU responsibilities and prior education on VAP. Institutional policies aimed at improving staffing levels and ongoing VAP education may enhance compliance and improve patient outcomes.